Synthesis and characterization of copper zinc oxide nanoparticles obtained via metathesis process - Weerachon Phoohinkong; Tita Foophow; Wisanu Pecharapa (My University, 2017)
Copper-doped zinc oxide nanoparticles were successfully synthesized by grinding copper acetate and zinc acetate powder with different starting molar ratios in combined with sodium hydroxide. The effect of initial copper and zinc molar ratios on the product samples was investigated and discussed. Relevant ligand coordination type of reactant acetate salt precursors and product samples were investigated by Fourier transform infrared spectroscopy (FTIR). The particle shapes and surface morphologies were characterized by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). Phase structures of prepared samples were studied by x-ray powder diffraction (XRD) and x-ray absorption near-edge spectroscopy (XANES) was applied to investigate the local structure of Cu and Zn environment atoms. The results demonstrate that the, particle size of as-synthesized products affected by copper concentration in the precursor trend to gradually decreases from nanorod shape with diameter around 50–100 nm to irregular particle structure around 5 nm associated with an increase in the concentration of copper in precursor. Moreover, it is noticed that shape and morphology of the products are strongly dependent on Cu:Zn ratios during the synthesis. Nanocrystallines Cu-doped ZnO by the substitution in Zn site with a high crystallization degree of hexagonal wurtzite structure were obtained. This synthesis technique is suggested as a potential effective technique for preparing copper zinc oxide nanoparticles with various atomic ratio in wide range of applications.
Keywords: XANES; Copper-based nanomaterials and applications